Partisipasi Penganggaran, Asimetri Informasi, Budaya Organisasi, Komitmen Organisasi dan Senjangan Anggaran - Nanda Narotama, I Dewa Gde; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 30 No 12 (2020)DO - 10.24843/EJA.2020.v30.i12.p02, 2020)
The purpose of this study is to empirically examine the effect of budgetary participation, information asymmetry, organizational culture and organizational commitment on budgetary slack. This research was conducted in all OPDs in Tabanan Regency. The number of OPDs used was 40 OPDs and the number of sample used by 120 peoples. The data analysis technique used is multiple linear regression analysis. The results of this analysis indicate that budgetary participation and information asymmetry have a positive effect on budgetary slack while organizational culture and organizational commitment have a negative effect on budgetary slack. This shows that the higher budgetary participation and information asymmetry results in higher budgetary slack, while higher organizational culture and organizational commitment results in lower budgetary slack rates. Keywords: Budgeting Participation; Information Asymmetry; Organizational Culture; Organizational Commitment; Budgetary Slack.